Distributing global health resources : Contemporary issues in political philosophy - Hassoun, Nicole; Herlitz, Anders (Philosophy Compass, 2019)
How should states and international organizations allocate global health resources? This paper examines proposals for distributing these resources in the literature. First, we look at the literature on the metrics for measuring what matters and consider how they might be modified to avoid some common objections—e.g., that these measures discriminate against the disabled or fail to give due weight to helping the young (or old) or those in present (or future) generations. Second, we canvas existing approaches to evaluating allocations of health-related resources utilizing such measures and advance a new way of doing so. We suggest that it is important to provide substantive arguments for directly evaluating alternative allocations, but there is also room for deliberation about fair procedures for selecting allocation criteria and securing just outcomes.